2017
DOI: 10.1515/pac-2016-1209
|View full text |Cite
|
Sign up to set email alerts
|

Studies on oxidative transformations of thiols, sulfides and alcohols in the presence of chlorine dioxide

Abstract: Our recent studies on the chemical reactivity of chlorine dioxide in the reactions with sulfur and oxygen containing compounds are reviewed. A special attention is given to chlorine dioxide interaction with alkyl, aryl, heteroaryl, monoterpenyl thiols, sulfides and disulfides. The data on the oxidation of monoterpene alcohols and phenols are also presented. The directions of reactions depending on the structure of the compounds were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Previously, the reactions of ClO 2 with alkane-, aryl-, hetaryl-, mono-, and diterpene thiols were studied [ 5 , 14 , 15 ]. It was shown that the main oxidation products are the corresponding disulfides, thiosulfonates, sulfonyl chlorides, and sulfonic acids, and in some cases, trisulfides, ketones, and sulfonic acid esters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the reactions of ClO 2 with alkane-, aryl-, hetaryl-, mono-, and diterpene thiols were studied [ 5 , 14 , 15 ]. It was shown that the main oxidation products are the corresponding disulfides, thiosulfonates, sulfonyl chlorides, and sulfonic acids, and in some cases, trisulfides, ketones, and sulfonic acid esters.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we used vanadyl acetylacetonate catalyst (VO(acac) 2 ) to increase the chemoselectivity of the process. We had previously shown its effect on the selectivity of the formation of thiosulfonates and sulfochlorides [ 14 ]. The presence of VO(acac) 2 in the reaction of disulfides 7 and (2 S )- 13 with an aqueous solution of ClO 2 in acetonitrile leads to an increase in the yields of thiosulfonates 14 and (2 S )- 15 from 20% to 74 and 81%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…36,37 Despite the availability of several reagents for the synthesis of thiosulfonates in the literature, only a few are applicable for one-pot direct oxidation of thiols to thiosulfonates. 4,28 Most of these methodologies suffer from several drawbacks such as complicated procedures for the synthesis of reagents, the need to activate reagents, use of hazardous chemicals, and expensive techniques. 4 Thus, general and facile protocols for direct oxidative transformation of thiols to thiosulfonates remain much sought after.…”
Section: Introductionmentioning
confidence: 99%
“…20 A number of methodologies have thus far been reported to access thiosulfonates. 4,12 Four main strategies followed for their synthesis are: i) from thiols or disulfides in the presence of oxidants with [21][22][23] or without [24][25][26][27][28] involvement of transition metals, ii) the addition of disulfides or thiols to sodium sulfonate, 29 iii) the reductive coupling of sulfonyl chlorides 16,30 and sulfonyl hydrazides with or without metal catalyst, [31][32][33][34] and iv) the reaction of sulfonyl halides 35 with other thiols or thiolates. 4,12 In addition, electrochemical methods are also known for the synthesis of thiosulfonates.…”
Section: Introductionmentioning
confidence: 99%
“…Terpene thiols can be used as intermediates in organic synthesis to produce sulfochlorides, [15–17] sulfonamides, [18] sulfides, [4,8,9,19] disulfides, [5,20] sulfenimines and sulfinimines [7,21–25] . Chiral monoterpene hydroxythiols can also be used as chiral ligands or organocatalysts in asymmetric catalysis and as chiral auxiliaries in asymmetric synthesis [26–36] .…”
Section: Introductionmentioning
confidence: 99%